A tolerância térmica como ferramenta para avaliação da vulnerabilidade de anfíbios ao aumento da temperatura - André, Thaís Cibele (2019)
Climate change can have major effects on biodiversity, forcing species to adapt or generating large extinctions for those that cannot cope with the direct and indirect effects of rising temperatures. In particular, larvae of amphibians are extremely dependent on water and have low thermoregulation capacity, being considered isothermal in relation to the medium. Therefore, measures of the thermal physiology of amphibians, associated with the present and optimal temperatures in which they are found, are a very useful tool to evaluate the vulnerability of the species, as well as they can be useful in the analysis of climate modeling and conservation strategies. In the present study, we used larvae of three species of phylogenetically close anuran amphibians (Physalaemus cuvieri, P. gracilis and P. henselii), but with different reproductive phenologies, to determine the thermal performance curves and indicate if they already face temperatures that may damage your performance. We used the growth of the larvae along six thermal acclimations representing temperatures in which the species already live in nature (15ºC, 20ºC 23.5ºC, 29ºC, 31ºC and 35ºC), to determine the optimum temperature and to construct thermal performance curves. We use microclimatic data recorded in nature to calculate the Thermal Safety Margin (TSM), Warming Tolerance (WT) and Cooling Tolerance (CT), as well as projecting a future temperature increase scenario (+4ºC). We used macroclimatic data to evaluate the relationship between air temperature and water temperature. The optimum temperature of Physalaemus cuvieri was 31°C, P. gracilis was 29 °C and P. henselii was 20 °C. Physalaemus gracilis and P. henselii already experience temperatures above the optimum recorded. Physalaemus henselii presented TSM more worrying in comparison to the other species, because it presented the lowest optimum temperature and was sensitive to the hotter acclimations. Physalaemus gracilis presented low WT, especially when we included the global warming scenario. Physalaemus cuvieri was the species most susceptible to cooling. With these results, we can understand how the performance curve of these species works and know which ones are most vulnerable to potential temperature increases and, in the future, try to design macro and microclimatic data together with physiological as tools to formulate conservation strategies.